Pembangunan Sentra Kreasi Desa Sebagai Wadah Aspirasi Menuju Desa Karangmekar Yang Sehat Dan Sejahtera - Suhrowardi; Iin Masriah; Enur Hotimah; Dede NI; Rahadian SA (LPPM STEBIS YPII, 2024)
Karangmekar Village is one of the locations considered suitable for carrying out community service. Karangmekar Village also has advantages in its geographical location. This potential should be developed as regional income, but this is not in line with the socio-economic development and welfare or education of the village community. This can be seen from the low percentage of the number of residents working as factory employees not because the industrial sector cannot absorb workers from Karangmekar Village, but rather because of the low work ethic of the local population, usually they do not last long working in the factory and leave without any clear work. The impact is that there is a socio-economic gap between the local population and the newcomers. The concept designed by the STEBIS YPII Community Service team to be implemented and developed in order to answer all the problems that arise in Karangmekar Village is